(3Cda HGAs - (3CHh GdMLGL GdHdhj , jhSa Hf eMeO Hf YHO Gddg Hf jMji Hf ZGdH,J (B604 (3g` s ((3eMeO Hf eMeO Hf eMeO GdRjGOj s)
(3ChdgG (B:s
(3CeG HYO(B: (3aEfj YReJ Ydi Cf CLeY gj gPg GdChQGb cd eYfi Qb Ch QGb, eeG gh YfOj eSJMSf dG eSJNTf heSJedM dG eSJbHM, hCKHJ ajg ef GdahGFO eG jRQj Ydi GdaQGFO s
(3BNQgG (B:s
(3hGdMeO ddg SHMGfg ef YGde ebJOQ Mqj Gddge CgOfG SHd GdSdGe jGPG GdLdGd hGdEcQGe hbO ced GdcJGH HYhf Gdedc GdhgGH s
(3GdfSNI HgG MhGTs
(3YdjgG HYV GdJYdjbGJs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B247 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B330s
Keywords: (3GdCOHs